Who influences policy? Analysing actor influence on the UK sustainable development strategy. (12th March 2007) - Ellis, Louise
Sustainable development is a multiactor concept, but who really has influence in the policy arena? A framework of influence has been devised to aid the identification and understanding of such influence, incorporating theories of power and discourse. This framework has been applied to the review of the UK sustainable development strategy, using the qualitative methods of observation, interview and discourse analysis. Through the use of the framework it is demonstrated that tacit influence is playing a significant role in policy development even in a situation where a detailed formal consultation process had been completed.